Therapy in Pediatric Dermatology Management of Pediatric Skin Disease - Teng, Joyce M.C.; Marqueling, Ann L.; Benjamin, Latanya T.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book addresses the need for comprehensive review of therapeutic options that are known to be efficacious in the management of cutaneous diseases in children. It summarizes evidence-based literature on clinical responses among pediatric patients, including age-appropriate management strategies. Included is review of the extraordinary developments in understanding of the genetics and pathogenesis of many cutaneous disorders during the past decade, the novel therapeutic options and repurposing of old drugs, and the management of some of the most challenging skin disorders. Therapy in Pediatric Dermatology: Management of Pediatric Skin Disease is a succinct, user-friendly, and up-to-date therapeutic dermatologic textbook for physicians who care for children with skin disorders. Each skin condition is discussed with investigative and treatment recommendations in mind and provided based on extensive review of the literature. This book will provide unbiased, yet concise, information that is valuable to practitioners who manage pediatric patients in their practices.
Overview of Dermatologic Care in Children -- Management of Skin Disorders of the Newborn -- Atopic Dermatitis and Eczematous Eruptions -- Psoriasis and Other Papulosquamous Skin Disorders -- Hereditary Disorders of Cornification -- Hereditary Disorders of the Dermis -- Disorders of Hair and Nail -- Disorders of the Sebaceous and Sweat Gland -- Cutaneous Tumor and Tumor Syndromes -- Histiocytosis and Malignancy -- Disorders of Pigmentation -- Vascular Disorders and Anomalies -- Genodermatoses and Basement Membrane Zone Diseases -- Infectious Diseases -- Viral Disease and Exanthems of the Skin -- Bites and Infestations -- Hypersensitivity Syndromes -- Photosensitivity and Photoreaction -- Collagen Vascular Diseases -- Inborn Metabolic Disorders and Endocrine Disorders -- Cutaneous Manifestations of Systemic Disease -- Cutaneous Manifestations of Psychologic Disorders and Management -- Pearls for Pediatric Dermatologic Procedures -- Light-Based Procedures in Pediatric Dermatology.
Keywords: Medicine; Dermatology; Pediatrics; Primary care (Medicine).; Medicine & Public Health; Dermatology; Pediatrics; Primary Care Medicine